An Empirical Study of Impact of Electronic Commerce on Business - Ahmadi, Ali Ahmad; Ahmad Baloch, Feroz; Mohammad Wafa, Khan; Naeem Dost, Mohammad (Journal of Information Systems and Technology Research, 2022)
The purpose of this study is to emphasize the influence and effect of E-Commerce on business. E-Commerce is purchasing and selling goods and services through the Internet. The company concept is developed to present its services online, allowing clients to choose and purchase the needed things. Web-based business is a way to do business through the Internet. E-Commerce has transformed the nature of business so swiftly and dramatically that what was once revolutionary is now just evolutionary. The study's primary goals are to research the idea and effect of E-Commerce, as well as to present the pros and downsides of E-Commerce. They are considering the study's aims, namely the success of E-Commerce and the challenges of the conventional company, which businesspeople encounter several issues daily. If you conventionally join the market, you will quickly find that competition is fiercer than ever, innovation is costly, and creating and recruiting a team is time-consuming. Solving difficulties and staying on top of the game have serious financial consequences for the firm. More preparation and even more cost-effective explanations are required for you as a business to approach the market. On the other hand, this study concentrates on performing sales and marketing online, which may be more productive than conventional methods. Finally, this article aims to examine E-Commerce's efficacy in contrast to conventional business.